The Quality of Public Service Innovations That Can Improve Services to the Community Through the GOMT Application in Gorontalo City - Leisyawati Ali; Asna Aneta; Zuchri Abbusamad; Yanti Aneta; Mohamad Afan Suyanto; Barmin Rahmat Yusuf (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Aims: The purpose of this study is to determine the quality of public service innovation that can improve services to the community through the GoMT application in Gorontalo City. Methodology: This study uses a qualitative research approach. Furthermore, the data traced includes primary and secondary data. The method used to determine the data source in this study is purposive sampling. The research location is within the scope of the City of Gorontalo, while the length of time the research uses is a period of 3 months. Results: The results of this study indicate that excellent service in public service innovation in the City of Gorontalo is currently considered sufficient while some people have not fulfilled the wishes of the service user community. get service but the drawback is that the service is not maximized due to the requirements that still burden the community who use the service in Gorontalo City.